2012
DOI: 10.1016/j.optcom.2011.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering under nanofocusing: Towards coherent nanoscopies

Abstract: We investigate light scattering under nanofocusing in the context of coherent spectroscopy. We discuss the different mechanisms that may enhance the signal in extinction and how these depend on nanofocusing as well as on the probed system. We find that nanofocusing may improve the detection sensitivity by orders of magnitude under realistic conditions, enabling scanning implementations of coherent spectroscopy at the nanoscale.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…This is different from the case of a laser pulses that propagate in a dispersive dielectric medium which experience pulse temporal broadening due to group velocity dispersion. This behavior has been also confirmed by means of numerical calculations by different authors [40,82,83].…”
Section: Excitation With Ultra-short Laser Pulsessupporting
confidence: 69%
See 2 more Smart Citations
“…This is different from the case of a laser pulses that propagate in a dispersive dielectric medium which experience pulse temporal broadening due to group velocity dispersion. This behavior has been also confirmed by means of numerical calculations by different authors [40,82,83].…”
Section: Excitation With Ultra-short Laser Pulsessupporting
confidence: 69%
“…Theoretical calculations have demonstrated that with direct coupling mechanism an overall efficiency as high as 70 % can be obtained. This result refer to a radially polarized beam focused at the base of the sharp 2 m long gold nanocone [82,83].…”
Section: Excitation With Ultra-short Laser Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of great interest [1][2][3][4][5][6][7][8][9][10][11][12][13] to devise techniques for reducing this limit, however, so that one might be able to locally control the interaction of the field with two or more atoms that are separated in space by a distance much less than this diffraction limit. Early work [3][4][5] on subwavelength localization, as this effect is called, was based upon spatially varying perturbations, such as a Zeeman shift caused by an inhomogeneous magnetic field or the ac Stark shift caused by the intensity gradient of the spatial profile of a focused laser beam.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 However, instead of considering the extinction, absorption and scattering from first principle as done by Mohammadi and Agio, 22 we choose to follow this classical treatment as it enables a clearer discussion of SNRs.…”
mentioning
confidence: 99%